Bridging the divide: reconciling stakeholder values for payment for ecosystem services. : A framework for sustainable management in Batticaloa Lagoon, Sri Lanka - Kulasegaram, Partheepan; Musthafa, Muneeb M.; Bhavan, Thangamani; Murgante, Beniamino (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Coastal lagoons are vital and productive ecosystems globally. However, recent anthropogenic pressures have substantially degraded these environments. The sustainability of lagoon resources critically depends on stakeholder engagement. Employing a choice experiment, this study quantifies the divergent preferences of key stakeholder groups–fishermen, tourists, and flood-affected residents–for preservation versus degradation scenarios in Sri Lanka's Batticaloa Lagoon. The survey targeted stakeholders using stratified sampling and reached 405 participants in the Batticaloa Lagoon Watershed (BLW). The analysis further assessed local perceptions of degradation and stakeholders' compensation expectations (WTA). The Choice Experiment and multinomial logit model identified significant conflicts between conservation valuations and compensation expectations. This novel empirical application directly compares within-subject Willingness-to-Pay (WTP) and WTA measures, revealing significant valuation asymmetries that complicate Payment for Ecosystem Services (PES) design. These results provide empirical evidence of pronounced preference diversity among lagoon users in the study area. This study argues that management decisions must account for heterogeneous stakeholder valuations, rather than universal conservation ideals. The findings demonstrate the inevitability of one-size-fits-all PES policy failure and propose a differentiated PES framework with tailored incentives for fishermen, tourists, and flood-affected residents.